MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN MENGGUNAKAN METODE KOOPERATIF NUMBERED HEADS TOGETHER (NHT) SISWA KELAS VB SDN 010 TEMBILAHAN HULU KECAMATAN TEMBILAHAN HULU - Maryatul Sakriyah (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The problem of the research is the low students output of class VB SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu. The learning problem was solved by applying Cooperative Heads Together (NHT) method, the research question is: Does the applying Cooperative Heads Together (NHT) method could improves the students output of IPS subject of class VB SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu? The purpose of the research is to improve the students output of IPS subject of class VB SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu by applying Cooperative Heads Together (NHT) method. This research can be used to give the benefit for the researcher, students and SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu. The result of classroom action research of IPS subject which is done on the students of class VB SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu can be concluded that; output cycle 1 increased than conventional learning. The average of output pre-cycle is 55,21 (enough); in cycle I, increased to 72,60 (good); in cycle II increased to 77,39 (good); the classical completeness of pre-cycle are 7 students (30,43%); cycle 1 are 16 students (69,56%); cycle 2 increased to 21 students (91,30%). 2 students which did not complete yet were joining the remedial. The result of the observation, students of class VB SDN 010 Tembilahan Hulu Kecamatan Tembilahan Hulu looked like understood about Cooperative Heads Together (NHT) method. They learnt the material in 4 - 5 student groups.